Efficiency of chewable toothbrush in reduction of dental plaque in students - Rasa Mladenovic; Andrijana Cvetkovic; Brankica Martinovic; Kristina Mladenovic; Milan Zivkovic; Zoran Arsic; Sasa Mladenovic; Tanja Zecevic Lukovic; Dragana Dakovic (BMC, 2019)
Abstract Background Besides classical and electrical toothbrushes market offers tooth brushes that can be chewed, like chewing gums. The aim of this study was to show the effectiveness of chewable toothbrush versus a conventional brush in the students' population. Methods The prospective study included 346 students. For this research, we used a e-questionnaire for "smart" phones, that students completed outside the dental office. Respondents are divided into two groups: control group used conventional toothbrushes, respondents from the tested group used chewable toothbrush. For assessment of accumulation of the plaque we used TQHI index. For testing statistical hypotheses, the following were used: t-test for two independent samples and analysis of the variance of repeated measurements. Results Before brushing teeth, the average TQHI value for chewable brushes is 2.8 ± 0.3, while conventional is 2.7 ± 0.3, which is not a statistically significant difference (p = 0.448). After brushing teeth, the average TQHI value for chewable brushes is 2.0 ± 0.1, while conventional 2.0 ± 0.3, which is also not statistically significant (p = 0.729). Observing the index of the plaque values on the tooth surfaces in the upper jaw, in both groups, there was a statistically significant change in the amount of plaque in time (p < 0.001). There is a statistically significant interaction between groups and changes in the amount of plaque in the observed period (p = 0.013). Conclusions The fact that there is no significant difference in the effectiveness of the tested brushes indicates the benefits of using chewable toothbrushes in order to reduce plaque, primarily in the inability to use conventional brushes.